Aplikasi Sistem Pendukung Keputusan Stadium Penyakit Kanker Payudara Menggunakan Logika Fuzzy Berbasis Android - Rico Adrial (STIKes Hang Tuah Pekanbaru, 2017)
Breast cancer treatable while still stadium early. The first step in the treatment of disease breast cancer is detection by true that symptoms appearing on the body patient is really cancer cells. Stadium cancer is the result of diagnostic by physicians so that ease in understanding for patients . On this research used fuzzy logic as a method that helps in making the support system of decision in determining stadium breast cancer. today much android applications are made in the provision of information in the field of health. By combining knowledge in the health sector , fuzzy logic and android is expected to become an application latest supporters of intelligible decision by many people on the health sector. The support system decision stadium disease breast cancer using fuzzy logic android based was designed . We can conclude that the application apply calculation based on fuzzy logic method sugeno and has been tested by calculation on matlab and manually.